Out-of-Pocket Expenditures of the Injured Patients Admitted in Casualty Unit of CMCH (Journal of Preventive and Social Medicine, 2023)
Background: Cost of treatment is a major concern in Bangladesh, as well as in many other lower- and middleincome countries and more than half of treatment cost is beard by the patient’s family which is out-of-pocket expenditures. The casualty unit of a hospital is the ultimate place for moderate to severely injured patients.Methods: A hospital-based cross-sectional study was commenced to estimate the out-of-pocket expenditures (OPE) incurred by the injured patients among 140 admitted injured patients. Data were collected by face-to-face interview through a pretested semi-structured questionnaire.Results: The mean age was 33.3±12.8 years and most of the patients (46.0%) resided in urban areas. The mean monthly family income was 26242.9±12698.9 taka. The majority of the patients had a single wound (71.4%), which was simple hurt (78.6%) in grading. The mean of the total direct costs was 8,936.5±9,437.7 taka and the mean of the total indirect cost was 2,057.0±3,189.9 taka. The mean of total OPE was 10,993.5±11,126.9 taka. Patient’s sex, residence and their grade of injuries (p